PL.60 Consequences of Failed Instrumental Deliveries- How Bad is It?. (26th April 2013) - Stephen, GL; Conroy, R; Vause, S; Tower, C
Abstract : Background: Unsuccessful instrumental delivery (ID) is typically associated with increased risks of adverse outcomes. We aimed to investigate the fetal and maternal consequences of failed instrumental deliveries in our unit. Methods: Data was collected prospectively as part of ongoing audit of all IDs performed in our unit between October 2008 and March 2012. Results: Complete records were available for 2664 IDs. Delivery was unsuccessful in 75 (2.8%). There was 1 maternal bladder injury and 1 hysterectomy. Unsuccessful ID was associated with increased blood loss (EBL), increased decision to delivery interval (DDI) and lower fetal Ph (p < 0.001 Mann-Whitney-U, table ). Sequential instruments were used in 189 (7%), and were successful in 182/189 cases (96%). Compared with successful use, unsuccessful sequential instruments were associated with higher blood loss, increased DDI and lower fetal Ph (p£0.06, Mann Whitney-U). Two fetal injuries occurred where sequential instruments failed compared to 3 injuries out of 68 unsuccessful deliveries where only 1 instrument was used (p = 0.07 fishers exact test). Conclusions: ID was associated with a low risk of failure, but failure was associated with worse outcomes. Although sequential instrument use was associated with the poorest outcomes, outcomes were better if vaginal delivery was achieved in this situation. This highlights the need for careful and competent use of instruments in the presence of experienced operators.